Cultural influences on doing qualitative research in public relations in Mexico - Daymon, Christine; Hodges, C. (School of Marketing, Curtin Business School, 2008)
Over the last decade in international public relations scholarship, there has been a significant growth in comparative research, offering illumination on the different practices, assumptions and expectations of those involved in public relations in both global and local contexts. The qualitative voice is increasingly heard because of its more nuanced insights on cultural difference. Yet there are significant challenges for researchers seeking to investigate public relations in cultures different from their own, one of the most prominent being how to explore and interpret in a culturally sensitive way the lived experiences of those under investigation. This is complicated by the intersection of the data with the researchers' own culture. To date, detailed accounts of the process of undertaking cross-cultural public relations research from an emic perspective are rare. In this paper, we join a long tradition in sociological research (Bell & Newby 1977) whereby we present an in-depth discussion of the process of conducting ethnographically-inspired research into the occupational culture of public relations in a Latin American city. The paper has a methodological focus, our aim being to raise issues concerning the conduct of cross-cultural, public relations research. Specifically, we examine how culture affected our decisions, methods and experiences when collecting data for a study of public relations practitioners in Mexico City.